Tricalcium phosphate-based capillary suspensions as inks for 3D printing of porous scaffolds - Souhaila Nider; Femke De Ceulaer; Berfu Göksel; Annabel Braem; Erin Koos (Open Ceramics)
Direct Ink Writing (DIW) has been extensively studied for creating hierarchical porous structures over recent decades. It finds applications in various fields, including aeronautics, industry, energy, and healthcare. On the other hand, capillary suspensions are an emerging field with significant potential for porous material development. These suspensions, typically three-phase systems, consist of solid particles interconnected by a secondary fluid (usually < 5 vol%), which is immiscible with the main one. Upon fluid removal and subsequent thermal treatment, they form a spanning particle network.This study explores the utilisation of β-TCP-based capillary suspensions as DIW inks for fabricating hierarchically porous scaffolds with two different secondary fluids. Rheological assessment of the inks demonstrates shear thinning behaviour, high yield stress, high moduli, and network rebuilding capabilities. While sucrose-based inks exhibit better printability, the ink incorporating silica nanoparticles exhibit structures with the highest porosity.